Implementation State Civil Apparatus (ASN) Core Values at RSUD Banten - Yeni Widyastuti; Tiwi Rizkiyani; Sierfi Rahayu (Jurnal Ilmiah Ilmu Administrasi Publik, 2023)
President Joko Widodo officially introduced the State Civil Apparatus (ASN) to core values and employer branding. As a public servant, policy implementer, and unifier of the nation, ASN plays a critical and strategic function, requiring unity of steps in the concept and work methods from the national government to local governments. The goal of these basic principles is to develop civil servants' culture so that they can operate professionally, particularly in the delivery of public services. The mentality issue in dealing with work pressure and change or disruption that necessitates a shift in thought and innovation has not been entirely resolved. A service-oriented mentality is one of the key values. RSUD Banten is one of the public-sector health-care organizations in Banten Province. With the establishment of RSUD Banten, it is envisaged that the needs of public health services in Banten Province can be satisfied to the greatest extent possible, one of which necessitates professional implementing human resources as service providers. The research method uses qualitative methods with a descriptive approach. Data analysis techniques using the model of Miles et al. The results showed that BerAKHLAK's core values have been implemented well by employees at RSUD Banten.